Pentingnya Pembelajaran IPS Terpadu untuk Penguatan Karakter pada Satuan Pendidikan di SMP - Mita Andira; Emilia Susanti; Istiqomah Wulan R; Muhammad Reza; Nurul Adila; Trisastia Wani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
The definition of Social Sciences (IPS) in Indonesia refers to the integrative study of human life in various dimensions of space and time and its activities. In the education sector, social studies refers to knowledge about the relationship between humans and their social environment. Character education, on the other hand, refers to a system of instilling character values ​​that includes the components of knowledge, awareness, and action to apply these values ​​in various contexts. The importance of character education in developing responsible, caring and empathetic individuals is emphasized in the culture and social environment concerned. The importance of integrated social studies includes several in-depth aspects, including a holistic understanding of the relationship between social science disciplines, development of critical and analytical thinking skills, development of social and emotional skills, and a broader understanding of human values, justice and democracy. Through various learning methods such as introduction to material, project-based learning, group discussions, case studies, simulations, and field visits, students can get to know integrated social studies well. After studying integrated social studies, students can show improvements in characteristics such as courtesy and responsibility. Through integrated social studies learning, students learn to respect cultural differences and be tolerant towards other people.